Is technical progress sectorally concentrated? An empirical analysis for Western European countries - Alexander Schiersch; Martin Gornig; Heike Belitz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Previous research shows that technical progress at the industry level, measured by sectoral TFP growth, is more localized in continental European countries than in Anglo-Saxon coun-tries. We use EU KLEMS data sets to decompose sectoral TFP for nine European countries by means of a Malmquist approach, in order to separate technical change. Applying Harberger diagrams, we describe the sectoral patterns of technical progress. The analysis reveals that in most European countries technological progress is much more evenly distributed across sectors than TFP.
Keywords: O14; O47; E23; 330